Penerapan Mirror Therapy untuk Mengatasi Gangguan Mobilitas Fisik pada Lansia dengan Kasus Stroke Non-Hemoragik : Application of Mirror Therapy to Overcome Physical Mobility Disorders in the Elderly with Non-Hemorrhagic Stroke Cases - Yuwono, Dian Kurniasari; Sandagang, Windy Syafitri; Dg.Mangemba; Nurarifah, Nurarifah; Sukmawati, Sukmawati; Galenso, Nitro; Hasan, Sri Musriniawati; Mangundap, Selvi Alfrida; Umar, Nurlailah (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2025)
Background: According to the Indonesian Health Survey, 35.4% of people between the ages of 65 and 74 had a stroke. A non-pharmacological technique called